TRAFFIC SIGNALS MODELLING WITH LONG DISTANCE COMMUNICATIONS USING PIC MICROCONTROLLER - Ahmet ÖZEK; Ömer KARAL (Pamukkale University Journal of Engineering Sciences, 2004)
Today, microcontrollers are widely used in control and automation systems. For the automation of traffic signalization, the crossroads need to be controlled by microcontrollers and for the automation of more than one crossroad the communication of more than one microcontroller is required. In some special cases, the intercommunication of microcontrollers is required to change crossroad status and obtain continuous flow (green weave) synchronization. In this study, a method is proposed to control the traffic flow on a hospital road with two crossroads located several km. apart from each other. For the purpose of changing the crossroads status to have a continuous flow of the traffic, the series of PIC16F877 microcontroller is used.